You shall understand what you regulate: A case study of the ANPD-Meta case in Brazil - Padua, Joao Pedro (Anais da Conferência Latino-Americana de Ética em Inteligência Artificial (LAAI-Ethics); 2024: Anais da 1ª Conferência Latino-Americana de Ética em Inteligência ArtificialDO - 10.5753/laai-ethics.2024.32471, 2024)
Regulating artificial intelligence is a primary need of current legal systems. However, bridging legal, policy and technical expertises to achieve good regulation is hard. We illustrate this difficulty by doing a short case study of a decision by the Brazilian Autoridade Nacional de Proteção de Dados–ANPD suspending Meta’s collection of data to train its large language models. I try to demonstrate that the lack of technical knowledge led the ANPD to issue a bad decision, that ended up backfiring. I end by discussing implications for regulatory best practices.